Prophylactic central lymph node dissection in cN0 papillary thyroid cancer: a comparative study of via breast and transoral approach versus via breast approach alone - Qiu, Rongliang; Fu, Jinbo (Frontiers in Endocrinology, 2024)
Background: Papillary thyroid cancer (PTC) progresses slowly and has a good prognosis, while the prognosis is worse if combined with central neck lymph node metastasis at an early stage. The different endoscope approaches may affect the thoroughness of lymph node dissection. This study aimed to compare the clinical efficacy and safety of prophylactic central lymph node dissection(CLND) for cN0 PTC performed via breast and transoral approach versus via breast approach alone.A retrospective analysis of the surgical data of 136 patients with stage cN0 PTC was performed from August 2020 to December 2022. Among them, 64 underwent the breast and transoral approach (combined approach group), and 72 underwent the breast approach alone (breast approach group). The relevant indexes of surgery, the number of lymph nodes dissected, the occurrence of postoperative complications, and the cosmetic satisfaction of incision were statistically compared between the two groups.The operative time of the combined approach group was 156.4±29.8 min, significantly longer than that of the breast approach group, 119.6±55.9 min, and the difference was statistically significant (P<0.05). The two groups of patients were compared in terms of intraoperative bleeding, postoperative drainage, hospitalization time, incision cosmetic satisfaction, and the occurrence of postoperative complications, and the differences were not statistically significant (P>0.05). The total number of lymph nodes retrieved in the central area (10.6 ±7.1) and the number of positive lymph nodes (4.6±4.9) in the combined approach group were significantly more than those in the breast approach group (7.4±4.8, 1.6±2.7), and the difference was statistically significant (P<0.05). The difference between the two groups in terms of the number of negative lymph nodes was not statistically significant (P>0.05).The study demonstrated that choosing the breast combined transoral approach for prophylactic CLND of cN0 PTC could more thoroughly clear the central area lymph nodes, especially the metastatic lymph nodes, which could help in the evaluation of the disease and the guidance of the treatment, while not increasing the postoperative complications. It provides a reference for clinicians to choose the appropriate surgical approach and also provides new ideas and methods for prophylactic CLND in patients with cN0 PTC.